Analysis of Iron (Fe) Content and PH Content of Protected Well Water in Leubok Village, Aceh Barat District - Jusriana Jusriana; Darmawan Darmawan; Maiza Duana; Sufyan Anwar (Universitas Teuku Umar, 2023)
The provision of clean water is still a major problem in Indonesia and one of the reasons is that the available raw water is still limited. Even though it is recognized that water sources are closely related to the nutritional status of children, including stunting. The research objective was to analyze the water quality in protected deep wells in Leubok Village, Aceh Barat District. The method used is descriptive with an observational approach and laboratory examination. Two water sources, namely water from a drilled well with a depth of 12 meters and water from a drilled well with a depth of 6 meters are the research samples. The results of the physical test showed that the water was colorless, odorless and tasteless in both water sources. In the water of the drilled well at a depth of 12 meters, it was found that the content of Fe was 0.16 Mg/L and the pH was 7.9 Mg/L, while the water in the well, which was 6 meters deep, was found to contain Fe 0.06 Mg/L and the pH of the water was 7.5 Mg/L. The conclusion that can be drawn is that the sources of clean water from both water sources in Leubok Village meet the standard of maximum concentration for clean water for hygiene and sanitation purposes, as well as the requirements for drinking water, especially the physical and chemical criteria (particularly pH and Fe). To be truly suitable for consumption, further studies are needed on microbiological parameters, inorganic chemical parameters, and other chemical parameters.